Enhancing the Cytocompatibility of Cobalt-Iron Ferrite Nanoparticles Through Chemical Substitution and Surface Modification - Chapa, Christian (2023)
Due to their potential in numerous interdisciplinary fields, such as drug delivery, hyperthermia, and magnetic resonance imaging, magnetic nanoparticles have attracted widespread attention. In this study, cobalt ferrite nanoparticles are synthesized with varying amounts of iron and cobalt ions, and their cytocompatibility is evaluated before and after surface modification with amino-silane (AEPTMS). Characterization of the synthesized nanoparticles is performed using scanning electron microscopy, energy-dispersive X-ray spectroscopy, X-ray diffraction, and Fourier transform infrared spectroscopy. In addition, it is observed that a slight reduction in the saturation magnetization of the coated materials. The cytotoxicity of these materials is evaluated using the MTT assay on fibroblast cells. This study focuses on the importance of the interface between the surface of magnetic nanoparticles, their coating, and their interaction with cells. This study presents an innovative approach to enhancing the cytocompatibility of cobalt ferrite nanoparticles through chemical substitution and surface modification with AEPTMS. The key findings demonstrate that the iron and cobalt ion ratio significantly impacts cytotoxicity, with the AEPTMS coating found to increase cell viability. These findings demonstrate the potential of these materials for biomedical applications, highlighting the importance of both the composition and surface coating of magnetic nanoparticles for biomedical applications.